2020
DOI: 10.1186/s12935-020-01411-8
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Long non-coding RNA SATB2-AS1 inhibits microRNA-155-3p to suppress breast cancer cell growth by promoting breast cancer metastasis suppressor 1-like

Abstract: Background Long noncoding RNAs (lncRNAs) and microRNAs (miRNAs) play vital roles in human cancers. Nevertheless, the effects of lncRNAs and miRNAs on breast cancer (BC) remain to be further investigated. This study was designed to testify the roles of lncRNA antisense transcript of SATB2 protein (SATB2-AS1) and microRNA-155-3p (miR-155-3p) in BC progression. Methods Levels of SATB2-AS1, miR-155-3p and breast cancer metastasis suppressor 1-like (BRMS1L) in BC were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“… 45 The lncRNAs in cytoplasm can bind directly to miR molecules, prevent them from binding to target genes, thereby upregulating expression of target genes. 46 lncRNAs can be used as “central platforms” to enable different macromolecular complexes to be assembled, thereby promoting information fusion and integration between different signaling pathways. 47 , 48 In addition, lncRNA can be used as secondary activators or enhancers for activation of target genes.…”
Section: Overview Of Lncrnasmentioning
confidence: 99%
“… 45 The lncRNAs in cytoplasm can bind directly to miR molecules, prevent them from binding to target genes, thereby upregulating expression of target genes. 46 lncRNAs can be used as “central platforms” to enable different macromolecular complexes to be assembled, thereby promoting information fusion and integration between different signaling pathways. 47 , 48 In addition, lncRNA can be used as secondary activators or enhancers for activation of target genes.…”
Section: Overview Of Lncrnasmentioning
confidence: 99%
“…The Editors-in-Chief have retracted this article [ 1 ]. Concerns were raised with a number of figures, specifically: Fig.…”
Section: Retraction To: Cancer Cell Int (2020) 20:321 101186/s12935-mentioning
confidence: 99%
“…Previous reports have illustrated that SATB2-AS1 is a critical regulator in some cancers. For example, some studies have confirmed that lncRNA SATB2-AS1 inhibits the growth of breast cancer cells by inhibiting miR-155-3p [ 9 ]. Xu M et al also illustrated that lncRNA SATB2-AS1 abated colorectal cancer (CRC) metastasis and affected the microenvironment of tumor immune cells by regulating SATB2 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%